Memahami Kronologi Sejarah Penyebaran Islam di Nusantara - Solihin, Moh. (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2017)
There are at least five theories that can be traced to the truth about the entry of Islam into Indonesia, namely Arabic theory, Gujarat theory, Persian Theory, Bengali Theory, and Chinese Theory. Whereas by whom Islam was brought about the entry process among historians there were also many versions put forward. Despite these differences, Islam developed massively in the archipelago. Al-Attas firmly believes that Western scholars who adopted Islam had no effect on the history of the people of the archipelago who made a fatal mistake in their analysis. Because the historical evidence found shows that the civilization of the archipelago actually found the color of Islam as written works in the Jawi script. If the history of the development of the spread of Islam in Indonesia was not interrupted by the colonial period, Islam in the archipelago would certainly have developed rapidly and would have been a blinding light after its dimming in the middle east.